How Dawson Read The City of God. - RHEIN, JACOB D. (Logos: A Journal of Catholic Thought & Culture)
In this article the author discusses St. Augustine's work "City of God," with two essays by Christopher Dawson, "The Dying World" and "The City of God." The author says that the basis for comparison is the way in which thinker confronts an epochal civilizational crisis with a Christian understanding of human nature.